Padangan Muhammad Said Al-Asymawi tentang Relasi Agama dan Politik - Abdillah Halim (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2021)
Nation building requires a cultural basis and platform as a basis for solidarity. In countries where the majority of the population is Muslim, religious aspirations and political movements must emerge. Certain strategies and handling are needed so that these Islamic aspirations are not counterproductive to national development. Muhammad Said Al-Asymawi's view on the relationship between religion and politics contributes a lot of understanding and clarification and becomes an important exemplar of the dynamics of thought so that fiqh siyasa rediscovers its relevance in the contemporary world. For Muhammad Said Al-Asymawi, Muslims need a fear of secularization in the sense of placing religion and politics in their respective places so that religion can manifest in life without being manipulated and reduced by politics. To arrive at this need requires a complete and adequate understanding of what he calls authentic Islam. His mastery of Islamic treasures and the history of Islamic development, makes his views on the relationship between Islam and politics difficult to refute and dispels the stigma of some people that he is a liberal thinker. Muhammad Said Al-Asymawi offers a scientific and authentic perspective on siyasa fiqh and makes siyasa fiqh actual and relevant again in the current situation and conditions.